Multidisciplinary approach to management of maternal asthma (MAMMA [copyright]): the PROTOCOL for a randomized controlled trial - Lim Angelina; Stewart Kay; Abramson Michael J; Walker Susan P; George Johnson (BMC, 2012)
Abstract Background Uncontrolled asthma during pregnancy is associated with the maternal hazards of disease exacerbation, and perinatal hazards including intrauterine growth restriction and preterm birth. Interventions directed at achieving better asthma control during pregnancy should be considered a high priority in order to optimise both maternal and perinatal outcomes. Poor compliance with prescribed asthma medications during pregnancy and suboptimal prescribing patterns to pregnant women have both been shown to be contributing factors that jeopardise asthma control. The aim is to design and evaluate an intervention involving multidisciplinary care for women experiencing asthma in pregnancy. Methods/design A pilot single-blinded parallel-group randomized controlled trial testing a Multidisciplinary Approach to Management of Maternal Asthma (MAMMA©) which involves education and regular monitoring. Pregnant women with asthma will be recruited from antenatal clinics in Victoria, Australia. Recruited participants, stratified by disease severity, will be allocated to the intervention or the usual care group in a 1:1 ratio. Both groups will be followed prospectively throughout pregnancy and outcomes will be compared between groups at three and six months after recruitment to evaluate the effectiveness of this intervention. Outcome measures include Asthma Control Questionnaire (ACQ) scores, oral corticosteroid use, asthma exacerbations and asthma related hospital admissions, and days off work, preventer to reliever ratio, along with pregnancy and neonatal adverse events at delivery. The use of FEV1/FEV6 will be also investigated during this trial as a marker for asthma control. Discussion If successful, this model of care could be widely implemented in clinical practice and justify more funding for support services and resources for these women. This intervention will also promote awareness of the risks of poorly controlled asthma and the need for a collaborative, multidisciplinary approach to asthma management during pregnancy. This is also the first study to investigate the use of FEV1/FEV6 as a marker for asthma control during pregnancy. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12612000681853)